PENGARUH KOMBINASI AROMATERAPI LAVENDER DAN GUIDED IMAGERY MUSIC (GIM) TERHADAP TINGKAT KECEMASAN PASIEN PRE OPERASI FRAKTUR DI RSUD NGUDI WALUYO WLINGI - Bachtiar, Achmad; Marsaid, Marsaid; Hidayah, Nurul; Diah Ciptaningtyas, Maria (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: Preoperative anxiety can occur in patients with fractures who are about to undergo surgery. If this anxiety is not addressed, it can affect surgical outcomes, including prolonged healing time and suboptimal results. Anxiety can be reduced through non-pharmacological techniques, one of which is the combination of lavender aromatherapy and guided imagery music (GIM). However, this technique is still not widely implemented in hospital wards. The aim of this study is to determine the effect of the combination of lavender aromatherapy and guided imagery music on the anxiety levels of preoperative fracture patients. Methods: The study design used is a quasi-experiment with a pre-test post-test control group design. The sampling technique used was purposive sampling, with a total of 64 respondents. Data were analyzed using the Wilcoxon test and Man-Whitney test. Results: The results of the study showed a change in anxiety levels before and after the administration of the combination therapy. In the treatment group, the average anxiety score before therapy was 16.19, and after therapy, the anxiety level decreased to a mild level with an average of 10.47, resulting in a difference of 5.72. Meanwhile, in the control group, the average anxiety score before therapy was 16.53, and after therapy, it was 16.28, with a difference of only 0.25. The statistical test results showed a significant effect on anxiety levels before and after the administration of the combination of lavender aromatherapy and guided imagery music, with a p-value of 0.000 < 0.005. Conclusion: The role of nurses is expected to include administering this combination therapy as a complementary therapy to help manage preoperative anxiety in fracture patients.